Developing the physical fitness of volleyball players using modern training equipment - Nikiforova, O.N.; Markin, E.V.; Soparev, A.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to substantiate the effectiveness of using training equipment in improving the special physical and technical training of volleyball players at the stage of intensive training. Methods and structure of the study. 38 volleyball players (9 candidates for master of sports, 12 first-class players, 15 second-class players, and 2 unranked players) from two teams at the agricultural university with different levels of training participated in the scientific work. One team of the second category participated in the student competitions of the higher league B, the second – of the first category in the Super League. The age of the players in each team ranged from 17 to 25 years. The training process was accompanied by the comprehensive use of training devices according to the author's methodology. The research programme involved studying the level of special speed and strength training using pedagogical tests and technical training using five tests performed with training devices connected to digital equipment. The data obtained was processed using special digital software for keeping statistics on training sessions. Results and conclusions. All indicators of special physical fitness are closely related to the growth of athletic skill. Correlation analysis has established that indicators of speed, speed-strength qualities, special endurance in jumping exercises, and indicators of hand and back muscle strength in both volleyball teams are closely related to the technique of attacking and blocking (r=0.48) as athletic skill improves. Research has proven the effectiveness of using training equipment in the digital processing of each training session, accounting for 40% of the annual training load at the advanced stage of volleyball training.